2013
DOI: 10.1007/s00394-013-0602-y
|View full text |Cite
|
Sign up to set email alerts
|

Plasma kinetics of chylomicron-like emulsion and lipid transfers to high-density lipoprotein (HDL) in lacto-ovo vegetarian and in omnivorous subjects

Abstract: Similarly to vegans, lacto-ovo vegetarian diet increases remnant removal, as indicated by cholesteryl oleate FCR, which may favor atherosclerosis prevention, and has the ability to change lipid transfer to HDL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 30 publications
1
13
1
8
Order By: Relevance
“…The higher consumption of MUFA and PUFA corroborates previous studies (Hawk, Englehardt & Small, 2012;Kristensen et al, 2015) as well as the higher ratio of unsaturated to saturated fatty acids (Majewska et al, 2016) and fiber intake (Vinagre, Vinagre, Pozzi, Zacari & Maranhao, 2014). However, no influence of this dietary pattern on plasma concentrations of total cholesterol were noted between the groups, contradicting studies that evidence this tendency when food of animal origin is restricted (Santos et al, 2013;Vinagre et al, 2014;Wang et al, 2015).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The higher consumption of MUFA and PUFA corroborates previous studies (Hawk, Englehardt & Small, 2012;Kristensen et al, 2015) as well as the higher ratio of unsaturated to saturated fatty acids (Majewska et al, 2016) and fiber intake (Vinagre, Vinagre, Pozzi, Zacari & Maranhao, 2014). However, no influence of this dietary pattern on plasma concentrations of total cholesterol were noted between the groups, contradicting studies that evidence this tendency when food of animal origin is restricted (Santos et al, 2013;Vinagre et al, 2014;Wang et al, 2015).…”
Section: Discussionsupporting
confidence: 86%
“…Findings regarding lipid profile, mainly HDL-c, in vegetarian groups are controversial. While some authors found no differences between vegetarians and non-vegetarians (Cedo et al, 2015;Santos et al, 2013;Vinagre et al, 2014) another study showed a significantly lower value of this parameter in vegetarians (Huang et al, 2012). Wang et al (2015) in a systematic review and meta-analysis showed that vegetarian diets, compared with omnivorous diets, improve therapeutic targets for cardiovascular disease risk reduction, including LDL-c.…”
Section: Discussionmentioning
confidence: 96%
“…In the subject of vegetarians, FCR cholesterol esters are five times higher than nonvegetarian, this indicates that the residual clearance of plasma kilomycron in vegetarians is more effective than nonvegetarian. The results of the study contradict the study of Lee et al, (2016) which states that there are no significant differences in total cholesterol levels between vegetarians and nonvegetarians, this is due to consumption of some food items that are still allowed in certain vegetarian groups such as vegetarian lacto ovo and ovo consuming eggs, while egg yolks are known to be one of the foods that are high in cholesterol, besides milk and milk products also contribute to the intake of saturated fatty acids and cholesterol (Vinagre et al, 2014).…”
Section: Discussioncontrasting
confidence: 72%
“…Vegetarian diets have a tendency to be low in saturated fatty acids (SFA) and rich in polyunsaturated fatty acids (PUFAs) which are known to have good effects on fat metabolism (McEvoy, Temple & Woodside, 2012). Vinagre et al, (2014) also suggested that the substitution of SFA with PUFA and MUFA would reduce LDL cholesterol levels through a mechanism to increase the expression of LDL receptors in liver cells and take leftover cholesterol by the liver. In a study by Vinagre et al, (2014) there were significant differences between Fraction Clearance Rate (FCR) cholesterol ester emulsions for vegetarians and nonvegetarians.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro post-heparin lipoprotein lipase (LPL) activity in the plasma was determined after 12 h fasting on the day after the kinetic studies [ 16 , 17 ], using as substrate a chylomicron-like emulsion labeled with glycerol tri[ 3 H] oleate. The plasma samples, collected 10 minutes after an injection of heparin (10U/kg BW), and the emulsion were incubated at 37°C for pre-established intervals during 180 min.…”
Section: Methodsmentioning
confidence: 99%